Constructing Religious Moderation and Multiculturalism: A Case Study of Pulukan Village, Jembrana Regency, West Bali - A.A. Ngurah Anom Kumbara; Nuning Indah Pratiwi; Susilo Edi Purwanto; I Wayan Suardiana (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
Jembrana Regency in West Bali is a multicultural region shaped by long-standing religious, ethnic, and cultural diversity, further reinforced by its historical ties with neighboring Java through migration and trade. Using Pulukan Village as a case study, this research examines how religious moderation and multiculturalism are constructed in everyday community life. The study employs a qualitative approach combining critical ethnography and ethnomethodology. Data were collected through participant observation, in-depth interviews, and document analysis involving religious leaders, customary leaders, village officials, and community members from diverse religious and ethnic backgrounds. The findings show that religious moderation is sustained not only through formal policies but also through everyday practices, including cooperation, interfaith participation in community activities, and dialogue-based conflict resolution. Multiculturalism is strengthened through continuous interaction, adaptation, identity negotiation, and mutual recognition of differences. This study demonstrates how locally rooted values and participatory community practices can foster social cohesion and provides insights for promoting religious moderation in other multicultural settings.